Diversity of Rickettsia in Ticks Collected in Abruzzi and Molise Regions (Central Italy) - Pascucci, Ilaria (Microorganisms, 2019)
Rickettsiae have worldwide occurrence and rickettsiosis are widely recognized as emerging infections in several parts of the world. For decades, it was thought that a single pathogenic tick-borne spotted fever group (SFG), Rickettsia, occurred in each continent. Nowadays, thanks to molecular biology, new species of Rickettsia responsible for disease in humans are continuously identified worldwide. In a framework of diagnostic activities of the Istituto Zooprofilattico Sperimentale dell’Abruzzo e del Molise “G. Gaporale” and considering some reports of suspected human clinical cases of rickettsiosis, a survey on ticks collected form animals and humans was carried out with the aim to identify the Rickettsia species circulating in Abruzzi and Molise regions. A total of 603 ticks, previously identified at species level by morphology, pooled into 178 tick samples, were tested by pan-Rickettsia RealTime PCR. DNA from specimens positive for Rickettsia spp. was then sequenced in order to identify the Rickettsia species involved. The highest infection rate was detected in Dermacentor marginatus followed by Ixodes ricinus. The selected targets for this purpose were OmpA and gltA. Rickettsia slovaca, Rickettsia monacensis, Rickettsia massiliae, Rickettsia conorii, Rickettsia aeschlimannii, Rickettsia helvetica, Rickettsia raoultii, and Rickettsia felis – like organisms were identified in this study. These are the first data available in the literature for the circulation of SFG Rickettsia species in the selected geographical area. Results made evidence of high rate of infection in ticks. All Rickettsia species detected have been previously involved in human infection. The diversity of Rickettsia detected, and tick species collected reflects the biodiversity in term of wildlife and environment of the area. An association between Rickettsia species, ticks, and the relationships with vertebrate host species are discussed. Due to the peculiar eco-biology of each Rickettsia species, the use of diagnostic tools able to identify Rickettsia at the species level is thus recommended in order to assess the risk for humans and to elucidate more precise etiological diagnosis in clinical cases.